Smart Territorial Development in Latvia: the Case of Zemgale Planning Region - Gemma, Sergejs; Vītoliņa, Zane (Socialiniai tyrimai, 2018)
Since 2013, Latvia has defined the smart specialization strategy at national level. In 2020, the planned outcome is the increased capacity of innovations including the share of high and medium-high technology sectors in the export; the number of researchers employed in the private sector; an increase in manufacturing productivity and share of innovative enterprises. The regional policy has the task to establish and implement local smart specialization strategies in order to achieve the planned results in country. Evaluating Zemgale planning region, it develops according to monocentric development at average national level.